Effects of an educational kickboxing program on students’ important role. Teachers and students’ perceptions - Menéndez Santurio, J.I.; Fernández-Río, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The goal of the study was to assess students and teachers’ perceptions after experiencing a kickboxing educational program (non-contact) and its effect on students’ important role. 60 students (15,4 ± ,90 años) and two teachers participated. A pre-experimental design with pretest-posttest measures and a case study was used. Assessment instruments: important role subscale of the Perceived Motivational Climate, open question to all students, photovoice and focus groups, teachers and observer’s diary, and students and external observer’s semi-structured interviews. After the intervention program, students’ perceptions of their important role significantly increased (F (59, 1) = 5,15, p = ,02). Seven themes emerged from qualitative data: learning, novelty, enjoyment, cooperation, friendship, inclusion and intention of future practice.